2016
DOI: 10.1080/00016489.2016.1218047
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-lymphocyte ratio and platelet-lymphocyte ratio as predictors of wound healing failure in head and neck reconstruction

Abstract: One hundred and three consecutive patients were enrolled. Among these, the results of 77 patients who were younger than 70 years of age were analyzed. The distributions of the neutrophil ratio (p = .0005), lymphocyte ratio (p = .0166), monocyte ratio (p = .0341), NLR (p = .005), and PLR (p = .008) differed significantly between the patients with and without post-operative wound healing failure. Neutrophil ratio, NLR, and PLR cut-off values of 64.9, 3.5, and 160 were significantly associated with the rate of wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
3
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 19 publications
2
37
3
3
Order By: Relevance
“…Serum albumin, a reliable indicator of nutritional status, remains an acceptable and simple method of predicting surgical complications . Neutrophil‐to‐lymphocyte ratio, a known indicator of systematic inflammatory burden, may be associated with an increased risk of surgical site infection . However, this systemic marker was not found to be a risk factor of fistula development in the present study.…”
Section: Discussioncontrasting
confidence: 61%
“…Serum albumin, a reliable indicator of nutritional status, remains an acceptable and simple method of predicting surgical complications . Neutrophil‐to‐lymphocyte ratio, a known indicator of systematic inflammatory burden, may be associated with an increased risk of surgical site infection . However, this systemic marker was not found to be a risk factor of fistula development in the present study.…”
Section: Discussioncontrasting
confidence: 61%
“…Because NLR is a known indicator of systemic inflammatory burden, increased NLR may be associated with an increased probability of surgical site infection, as shown in the current study. A controversial report showed that patients with lower preoperative neutrophil ratio, NLR, and PLR tended to have a higher rate of postoperative failure of wound healing . It was suggested that the altered status of homeostasis leads to a decrease in neutrophil ratio and NLR because of the shorter lifespans of neutrophils compared with lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…A controversial report showed that patients with lower preoperative neutrophil ratio, NLR, and PLR tended to have a higher rate of postoperative failure of wound healing. 40 It was suggested that the altered status of homeostasis leads to a decrease in neutrophil ratio and NLR because of the shorter lifespans of neutrophils compared with lymphocytes. Upon injury, neutrophils migrate to the wound during the inflammatory period via chemotaxis and endocytose proteolytic enzymes from intracellular granules for bactericidal action and the purification of necrotized tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The PRISMA flow chart of the systematic review can be found in Figure . An initial search done using the search strategy (Supporting Materials) obtained an initial 900 results.…”
Section: Methodsmentioning
confidence: 99%